A Short Review of Some of the Demarcational Problems Between Older and Revival Bosniac Literature: From Literature in Oriental Languages to Literature Created in Native Language (Prilozi za orijentalnu filologiju, 2017)
This paper gives a short review of the problematics of the demarcation between older literature and Bosniak Renaissance literature from the aspect of the observation of the changes in the Bosniak literature in Oriental languages in the second half of the 19th century. The review is directed in two ways: a) it points to some changes in the very poetics of the Diwan literature, including other poetical and literary directions in the unity of the Bosniak literature in Oriental languages; b) it describes the reflection of different “social changes” in the enlightenment-transitional period, in the middle of the 19th century, on the example of the relation towards the writing of the certain kinds of literature and literary genres in the literatures in Oriental languages in the Bosnian vilayat. A special focus is on the question of the Diwan poetry reception by the poets who wrote in Ottoman Turkish during the post-Tanzimat period, on the one hand, that is, on the period of the canonization of the reception of the Bosniak literature through the work of Safvet-beg Bašagić and later literary historians and theorists.